THE HERITAGE AND PUBLIC ARCHAEOLOGICAL: ARCHAEOLOGY IN URBAN AREA, THE LOWER CHILLON VALLEY - Raymondi Cárdenas, Antonio (2015)
This paper deals with the experiences as students on social and cultural realities of the urban population, acquired under the «Archaeological Research Project, Chillon-2014», excavations of 4 sites comprising: Huaca Pro (district of Los Olivos), Huaca El Retablo and Alborada 1 and 2 (district of Comas). Without good character was purely research project, we were not free to know and understand the social reality around and articulates with the archaeological heritage (Archeology-Public).